SOCIAL CAPITAL FOR BIDADARI BEACH TOURISM DEVELOPMENT - Aisyah Anggun Lestari; Alfitri; Diana Dewi Sartika (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2025)
This study aims to analyze the form and role of social capital in the management of the Pantai Bidadari tourist attraction by BUMDes Sepakat Sejahtera in Subik Village, Buay Pematang Ribu Ranau Tengah District, South OKU Regency. The research method used is qualitative with a case study approach. Data were collected through observation, in-depth interviews, and documentation, then analyzed using Robert Putnam's social capital theory which includes three main dimensions: trust, networks, and norms. The results of the study indicate that social capital plays an important role in building collaboration between managers, communities, and village governments. The form of trust is reflected through the involvement of local communities in managing and accepting village policies. Social networks are formed through mutual cooperation, socialization activities, and participation in youth organizations. Social norms develop through obedience to local rules in maintaining coastal sustainability. Social capital is a driving force in strengthening community participation and supporting the sustainability of tourism management. This study emphasizes the importance of strengthening social capital as a strategy for empowering and developing sustainable community-based tourism.